Overcoming Marketing Communication Challenges in Startup Companies - Iing Saefudin (Sean Institute, 2024)
Startups are companies that operate in a dynamic environment with unique challenges, including in marketing communications. This study aims to identify and analyze the marketing communication challenges faced by startup companies, and to offer effective strategies to overcome them. The research method used is a descriptive qualitative approach, with data collection through in-depth interviews, case studies, and literature analysis. The results of the study indicate that startup companies face a number of challenges in implementing effective marketing communications, including budget constraints, difficulties in building brand awareness, and challenges in conveying the unique value of the product to the audience. However, startups can overcome these challenges by utilizing more cost-effective digital platforms, optimizing the use of data to assess marketing results, and maintaining flexibility in adapting to rapid market changes. Success in marketing communications also depends on the startup's ability to design creative and responsive campaigns to market needs, which in turn can support their growth and competitiveness in a competitive market.